Revitalization of prefabricated housing. Implementation of European solutions to Polish conditions - Szpytma, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The problem regeneration of prefabricated housing in Poland is invariably the current issue. Due to a housing shortage, the demand for apartments in pre-fab housing is still high. Western Europe has begun to struggle with this problem much earlier and has a large experience in the subject of revitalization. However, the context of socio - economic development in Poland, different from the Western European, makes the transfer of complete solutions revitalization impossible . Presented examples show different strategies used in the past and now in Europe (housing revitalization Bijlmer in Amsterdam and building in Halle - Neustadt). They were based on the demolition to a lesser or greater extent. The difficult housing situation in Poland, related to the lack of sufficient amount of housing, poor infrastructure of social housing and complicated housing ownership structure of the buildings, mostly excludes demolition. However, the quality of prefabricated housing living could be significantly improved, without the need for demolition, as evidenced by the spectacular example of the revitalization of the Parisian skyscraper Tour Bois le Prêtre.